A Predictive Web-Based Nomogram for Elderly Patients Newly Diagnosed as Uveal Melanoma: A Population-Based Study - Lv, Meng; Yan, Xinhua; Tu, Yuanxing (Frontiers in Medicine, 2022)
Background: There is a lack of a comprehensive investigation concerning survival prediction for elderly patients with uveal melanoma (UM). This study aims to develop a nomogram and an individualized web-based calculator to predict the overall survival (OS) of elderly patients with UM. Methods: Patients diagnosed with UM who older than 60 years were searched from the Surveillance, Epidemiology, and End Results (SEER) during the time of 2004 to 2015, then randomly divided into training and validation cohorts. In the training cohort, the univariate and multivariate Cox analysis were carried out to determine the independent prognostic factors and the results were integrated to establish a nomogram for prediction of the 1-, 2-, and 3-year OS of elderly patients with UM. The discrimination of the nomogram was validated by receiver operate curves (ROC) and the area under the curve (AUC). The clinical practicability and accuracy of the nomogram were evaluated by the calibration curve and decision curve analysis (DCA). A web-based survival calculator was then constructed using a fitted survival prediction model. Results: A total of 1427 UM patients were included in this study, age, T stage, N stage, M stage, marital status sex and radiotherapy were identified as independent prognostic factors. Based on the above-mentioned factors, the nomogram was then constructed. The AUC values of the nomogram of OS at the time of 1-, 2- and 3-year was 0.751, 0.738 and 0.736 in training cohort, and 0.772, 0.763 and 0.766 in validation cohort. The calibration curves and DCA also indicated the well performance of the predictive model. Conclusion: The current study have established and validated a novel nomogram risk stratification model and a web-based survival rate calculator that can dynamically predict the long-term OS for elderly patient with UM